TRICARBONYLCHROMIUM(0) PROMOTED STEREOSELECTIVE TRANSFORMATIONS OF EPHEDRINE AND PSEUDOEPHEDRINE DERIVATIVES - Coote, S; Davies, S; Goodfellow, C; Sutton, K; Middlemiss, D; Naylor, A (1990)
(-)-(1S,2S)-(N,O-Dimethylephedrine)tricarbonyl chromium(0) (6) and (-)-(1S,2R)-(N,O-dimethylpseudoephedrine)tricarbonylchiromium(0) (22) undergo completely stereoselective ortho deprotonation upon treatment with alkyllithium base, followed by addition of an electrophile. In both cases, exclusive removal of the pro-(R)-ortho proton was confirmed by single crystal X-ray structure analyses of the methylated products. Addition of methyllithium onto the ortho-formylated derivative of complex (6) occurs stereoselectively, the stereochemistry of the major product being confirmed by a single crystal X-ray structure determination. The results presented demonstrate an efficient transfer of chirality from a side chain onto the (arene)tricarbonylchromium(0) complex and back to a different side chain. © 1990.